Outcome of children treated for relapsed acute lymphoblastic leukemia in Central America. Issue 6 (16th November 2012) - Marjerrison, Stacey; Antillon, Federico; Fu, Ligia; Martinez, Roxana; Vasquez, Roberto; Bonilla, Miguel; Howard, Scott C.; Sung, Lillian
Abstract BACKGROUND: Outcomes for relapsed childhood acute lymphoblastic leukemia (ALL) have not been documented in resource‐limited settings. This study examined survival after relapse for children with ALL in Central America. METHODS: A retrospective cohort study was performed and included children with first relapse of ALL in Guatemala, Honduras, or El Salvador between 1990 and 2011. Predictors of subsequent event‐free survival (EFS) and overall survival (OS) were examined. RESULTS: There were 755 children identified with relapsed disease. The median time from diagnosis to relapse was 1.7 years (interquartile range, 0.8‐3.1 years). Most relapses occurred during (53.9%) or following (24.9%) maintenance chemotherapy, and the majority occurred in the bone marrow (63.1%). Following the initial relapse, subsequent 3‐year EFS (± standard error) and OS were 22.0% ± 1.7%, and 28.2% ± 1.9%, respectively. In multivariable analysis, worse postrelapse survival was associated with age ≥ 10 years, white blood cell count ≥ 50 × 109/L, and positive central nervous system status at the original ALL diagnosis, relapse that was not isolated central nervous system or testicular, and relapse < 36 months following diagnosis. Site and time to relapse were used to identify a favorable risk group whose 3‐year EFS and OS were 50.0% ± 8.9% and 68.0% ± 8.1%, respectively. CONCLUSIONS: Prognosis after relapsed ALL in Central America is poor, but a substantial number of those with favorable risk features have prolonged survival, despite lack of access to stem cell transplantation. Stratification by risk factors can guide therapeutic decision‐making. Cancer 2013. © 2012 American Cancer Society.